Bunga Bank dalam Pandangan Nahdlatul Ulama dan Muhamadiyah serta Implikasinya terhadap Undang Undang Perbankan: Studi atas Epistemologi Hukum Islam - Supriyatin; Kaimudin, Kaimudin; Misno, Misno (Tasyri' : Journal of Islamic Law, 2023)
Nahdlatul Ulama (NU) is an organization that combines traditionalism and accommodationism with the concept of "Aswaja" as its main way of thinking. NU uses three methods (qawliy, ilhaqiy, and manhajiy) in answering legal problems. On the other hand, Muhammadiyah is an organization that emphasizes tajdid (renewal) and ijtihad in the understanding of Islam, using the methods of ijtihad bayaniy, ijtihad qiyasiy, and ijtihad al-istislahiy.  This research uses literature methods and legal approaches with primary data sources in the form of fatwas of NU, Muhammadiyyah, and banking laws, as well as secondary sources in the form of books, journals, and documents related to the research theme. This article concludes that there are different methods of determining the law on bank interest, NU uses the ilhaqi method, while Muhammadiyah uses qiyas. These differences give birth to the dynamics of legal determination due to differences in methodology. The decision of NU  and  Muhammadiyah despite various polarizations (points of similarity and difference) in the process of determining bank interest law. Thesefatwas, directly or indirectly, through the MUI ultimately have implications for Law No. 7 of 1992 concerning Banking